Nature contact, nature connectedness and associations with health, wellbeing and pro-environmental behaviours. (April 2020) - Martin, Leanne; White, Mathew P.; Hunt, Anne; Richardson, Miles; Pahl, Sabine; Burt, Jim
Abstract: Contact with, and psychological connectedness to the natural world are both associated with various health and sustainability-related outcomes. To date, though, the evidence base has been fragmented. Using a representative sample of the adult population of England (N = 4, 960), we investigated the relationships between three types of nature contact, psychological connectedness, health, subjective wellbeing and pro-environmental behaviours within a single study. We found that specific types of nature contact, as well as individual differences in nature connectedness, were differentially associated with aspects of health, well-being and pro-environmental behaviours. Living in a greener neighbourhood was, unrelated to any wellbeing or sustainability outcomes. By contrast, visiting nature ≥ once a week was positively associated with general health and household pro-environmental behaviours. Moreover, people who watched/listened to nature documentaries reported higher levels of both pro-environmental behaviours. Nature connectedness was positively related to eudaimonic wellbeing and both types of pro-environmental behaviour. Moreover, connectedness moderated key relationships between nature contact, wellbeing and pro-environmental behaviours. The complexity of our findings suggests that interventions increasing both contact with, and connection to nature, are likely to be needed in order to achieve synergistic improvements to human and planetary health. Highlights: Visiting nature ≥ once/week was associated with better health. Nature connectedness was positively related to eudaimonic wellbeing. Nature connectedness was positively associated with pro-environmental behaviours. Nature documentaries were positively associated with pro-environmental behaviour. Connectedness moderated relationships between nature contact and outcome variables.